Using fruit flies to delve into mosquito insecticide resistance - Hossain, Kaniz Fatima Binte; Vimal, Divya; Owusu-Ansah, Edward (Frontiers in Malaria, 2023)
With more than 3,000 species and an almost ubiquitous presence, the economic importance of mosquitoes cannot be overemphasized. Anopheles mosquitoes are vectors for infectious diseases such as malaria – an endemic disease in tropical and sub-tropical regions of the world that infects more than 200 million people worldwide and causes over 400,000 deaths annually, with most casualties being infants or inhabitants of sub-Saharan Africa. The Aedes aegytpi and Culex quinquefasciatus species of mosquitoes are also vectors for arboviruses such as chikungunya virus, dengue virus, western equine encephalitis virus, and Zika virus. Consequently, insecticides are frequently used to stem the population of mosquitoes. Nevertheless, mosquito insecticide resistance has emerged as a major problem that has contributed to numerous failed eradication campaigns for the aforementioned diseases. In this mini-review, we expound on how fruit flies (Drosophila melanogaster) could be a complementary model system for studying mosquito insecticide resistance, with the ultimate goal of confirming any promising leads in mosquitoes.